Development of Human Resource Management Information System to Improve Employee Performance Efficiency and Effectiveness - Oktaviannur, Moh.; Kindiasari, Aktansi (International Journal of Artificial Intelligence Research, 2024)
The development of a Human Resource Management Information System (HRMIS) aims to enhance the efficiency and effectiveness of employee performance. This study focuses on designing and implementing an integrated HRMIS that automates various HR functions such as recruitment, attendance tracking, performance evaluation, and employee development. By leveraging advanced information technologies, the HRMIS provides real-time data and analytics, facilitating informed decision-making and strategic planning for HR managers. The system's user-friendly interface ensures ease of use and accessibility, promoting higher adoption rates among employees and management. Empirical data collected from case studies and surveys conducted within organizations demonstrate significant improvements in operational efficiency, reduced administrative burden, and enhanced employee satisfaction and productivity. The findings suggest that a well-implemented HRMIS can be a critical tool in optimizing human resource processes, aligning HR strategies with organizational goals, and ultimately driving overall business performance. Future research should explore the integration of emerging technologies such as artificial intelligence and machine learning to further enhance the capabilities of HRMIS.